Histochemical and Immunohistochemical Characterizations of Hepatic Trematodiasis in Odontocetes - Nakagun, Shotaro; Kobayashi, Yoshiyasu (Frontiers in Veterinary Science, 2020)
Hepatic trematodiasis is a common condition in a number of free-ranging cetacean species, which occasionally result in severe hepatic and/or pancreatic lesions. However, even the basic pathologic information of this disease is unknown for the majority of affected species. The current study describes and compares the histomorphology and immune reaction induced by hepatic trematodes of the family Brachycladiidae in the liver of the harbor porpoise (Phocoena phocoena, n = 8), Dall’s porpoise (Phocoenoides dalli, n = 8), and Hubbs’ beaked whale (Mesoplodon carlhubbsi, n = 2). Immunohistochemistry for 8 antibodies (CK19, CD3, Foxp3, CD20, Iba1, CD68, CD163, and CD204) were conducted to analyze the pathology of these parasitic infections. In all 3 odontocete species, the changes observed in the trematode-affected biliary epithelium were comparable with marked hyperplasia and goblet cell metaplasia, as well as lymphoplasmacytic and eosinophilic inflammation. Additionally, regions of the Glisson’s sheath were diffusely and severely fibrotic in all examined species, regardless of the physical presence of trematodes. Differences among the 3 species included the presence of characteristic lymphoid follicles formed in the fibrotic bile duct walls of only the 2 porpoise species. In the Hubbs’ beaked whale, the degree of lymphoplasmacytic cholangitis was more severe and ductular reaction was generally more prominent. In terms of the overall macrophage population among the 3 species, CD163- and CD204-positive cells (M2 macrophages) outnumbered Iba1- and CD68-positive cells (M1 macrophages), indicating a chronic infection stage in all analyzed individuals. Species-specific differences among the infiltrating macrophages included numbers of CD68-positive cells being significantly more abundant in the harbor porpoises, whereas CD163-positive cells were significantly more numerous in the Dall’s porpoises. The numbers of CD204-positive macrophages were higher in the Hubbs’ beaked whales compared to the porpoises. Trematode species of the harbour and Dall’s porpoises were Campula oblonga, while they were Oschmarinella macrorchis in the Hubbs’ beaked whales. This study concludes that interspecies differences in the tissue reactions to hepatic trematode infections are present among odontocete species, and that the immune reaction varies depending on the species. This information aids in furthering our understanding of the pathogenesis of hepatic trematodiasis in cetaceans.